The Relevance of God's Covenant for a Reformed Theology of Religion - Dirk Griffioen (Societas Dei: Jurnal Agama dan Masyarakat, 2016)
ABSTRACT: In God's Revelation, the structure of the covenant consists of God's promises and Israels answer to them. In the covenant God has revealed Himself personally to both individuals and his chosen people. In the theology of religion developed by Hendrik Kraemer, there are two types of religion: The (prophetic) religion based on Gods revelation and the other (naturalist) religions are based on efforts to grasp the identity of his real self with divine reality, this is called as trans-empirical self realization. What is the essence of religion based on God's self revelation? God's revelation is the only source of all knowledge about true spirituality and the salvation in Christ. The Bible as the witness of God's revelation to prophets and apostles is the criterion of all religious truth. The Bible relates the history of redemption, gives a foundation to personal faith, and is the only guidebook to the life and work of the Christian community. From this starting point I try to analyze the Biblical concept of religious truth as the standard for determining religions, and to give a real answer to Gods self revelation. KEYWORDS: covenant, revelation, faith, religion.